VÁZQUEZ GARCÍA, Francisco. (2018). Georges Canguilhem. Vitalismo y Ciencias Humanas. Cádiz: Editorial UCA, 199 páginas. - Diego Delgado Pastor (Daimon)
Recensión de: VÁZQUEZ GARCÍA, Francisco. (2018). Georges Canguilhem. Vitalismo y Ciencias Humanas. Cádiz: Editorial UCA.